2016
DOI: 10.1111/cob.12142
|View full text |Cite
|
Sign up to set email alerts
|

Energy intake highs and lows: how much does consistency matter in weight control?

Abstract: Summary Behavioural weight control programmes recommend adherence to daily energy intake goals, yet also allow for flexibility in intake across days. Evidence is lacking as to whether intake consistency is important for weight control. The current study explored the relation between day-to-day intake consistency and weight loss in the context of behavioural weight loss treatment and examined the relationship between variability in intake and several factors known to be associated with weight control success. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Further, the emerging literature suggests that particular dietary behaviours are associated with reduced cardiometabolic and psychological health. High snacking frequencies, a diminished fasting period and large day-to-day energy intake variability have been linked with weight gain [13], increased percent body fat [14], obesity [15,16,17], central obesity [18], decreased stress resistance [19] and increased risk of psychiatric disorders [20].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the emerging literature suggests that particular dietary behaviours are associated with reduced cardiometabolic and psychological health. High snacking frequencies, a diminished fasting period and large day-to-day energy intake variability have been linked with weight gain [13], increased percent body fat [14], obesity [15,16,17], central obesity [18], decreased stress resistance [19] and increased risk of psychiatric disorders [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to an association between perceived stress and weight regain, some studies have shown tendency towards irregular eating patterns among individuals reporting higher levels of stress, an eating behaviour referred to as 'stress eating' (13)(14)(15). This could theoretically lead to a higher degree of fluctuation in caloric intake and thereby promote a higher body weight variability (BWV), which by itself has been suggested as a predictor of future weight gain (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%